Respuesta :

Answer:

12.

Step-by-step explanation:

Average rate of change = (value of the function when x = 9 - value when x=3)

/

(9 - 3)

= f(9) - f(3) / (9-3)

= (9^2 - 3^2) / (9-3)

= 72 / 6

=  12.

The average rate of change of a function is the rate at which the y-values change over the x-values.

The average rate of change of [tex]f(x) = x^2[/tex] between (3,9) is 12.

Given that:

[tex]f(x) = x^2[/tex]

Where:

[tex]x_1,x_2 = 3,9[/tex]

The average rate (m) of change is calculated as follows:

[tex]m = \frac{f(x_2) - f(x_1)}{x_2 - x_1}[/tex]

This gives:

[tex]m = \frac{f(9) - f(3)}{9 -3}[/tex]

[tex]m = \frac{f(9) - f(3)}{6}[/tex]

Calculate f(9) and f(3)

[tex]f(x) = x^2[/tex]

[tex]f(9) =9^2 = 81[/tex]

[tex]f(3) =3^2 = 9[/tex]

So, we have:

[tex]m = \frac{81 - 9}{6}[/tex]

[tex]m = \frac{72}{6}[/tex]

[tex]m =12[/tex]

Hence, the average rate of change is 12.

Read more about average rates of change at:

https://brainly.com/question/23715190